(untitled) (Konferensiyalar | Conferences, 2024)
In the evolving landscape of teacher education, understanding ethnic and cultural dynamics is vital. This article explores how regions like the United States and Eastern Europe approach cultural diversity in teacher training. National policies, influenced by historical legacies, impact the integration of cultural elements. Initiatives by organizations like UNESCO prioritize cross-cultural understanding, essential for educators to thrive in diverse classrooms.